Paeoniflorin inhibits the macrophage-related rosacea-like inflammatory reaction through the suppressor of cytokine signaling 3-apoptosis signal-regulating kinase 1-p38 pathway. Issue 3 (22nd January 2021) - Liu, Zijing; Zhang, Jiawen; Jiang, Peiyu; Yin, Zhi; Liu, Yunyi; Liu, Yixuan; Wang, Xiaoyan; Hu, Liang; Xu, Yang; Liu, Wentao
Abstract : Abstract: Rosacea is a facial chronic inflammatory skin disease with immune and vascular system dysfunction. Paeoniflorin (PF) is a traditional Chinese medicine with anti-inflammatory properties. However, its effects on rosacea remain unknown. Here, we investigated the mechanisms through which PF inhibits the macrophage-related rosacea-like inflammatory response. Immunohistochemical methods were used to detect differences in the inflammatory response and degree of macrophage infiltration in granulomatous rosacea lesions and their peripheral areas. Cell Counting Kit-8 was used to determine the cytotoxicity of PF towards RAW 264.7 cells. Reverse transcription-quantitative polymerase chain reaction and western blotting were used to measure the influence of PF on mRNA and protein expression levels of suppressor of cytokine signaling 3 (SOCS3), apoptosis signal-regulating kinase 1 (ASK1)-p38, Toll-like receptor 2, and cathelicidin antimicrobial peptide ( or LL37) in the lipopolysaccharide (LPS)-induced macrophage-related rosacea-like inflammatory response of RAW 264.7 cells. Inflammatory cell infiltration was more pronounced in granulomatous rosacea lesions than in peripheral areas. LL37 expression increased significantly, and the infiltration of a large number of CD68 + macrophages was observed in the lesions. PF promoted SOCS3 expression in RAW 264.7 cells and inhibited the LPS-induced increase in toll-like receptor 2 and LL37 expression through the ASK1-p38 cascade, thereby alleviating the macrophage-related rosacea-like inflammatory response. These changes could be abrogated by SOCS3 siRNA in vitro. In conclusion, the pathogenesis of rosacea involves abnormal macrophage infiltration within the lesions. PF inhibits the macrophage-related rosacea-like inflammatory response through the SOCS3-ASK1-p38 pathway, demonstrating its potential application as a novel drug for rosacea therapy. Abstract : Supplemental Digital Content is available in the text